The Balinese Ethnic Community's Perceptions in Regards to Modifications in Denpasar's Residential Building Spatial Planning - I Kadek Merta Wijaya; Mariana Correia; I Nyoman Warnata; I Ketut Sugihantara (Universitas Sebelas Maret Surakarta, 2022)
The increase influences changes in the spatial layout of Balinese ethnic residences in Denpasar in the number of family members, the growth in the community's economy, and the availability of residential yard land, which is decreasing. On the one hand, the Balinese ethnic community in Denpasar still has a perception of direction and orientation of significant (high) and obnoxious (low) values or luan and teben orientations as the forerunner to the spatial configuration of Balinese ethnic residences with the concept of zoning of the Sanga Mandala tread. This study aims to conceive of the Denpasar community's perception of the arrangement of residential houses amid increasing residential space needs. The method used is descriptive qualitative through empirical studies by conducting in-depth observations and interviews to understand the Denpasar community's understanding of structuring their homes. This study found that the Balinese ethnic community perceives changes in their homes' spatial layout based on literacy and adaptation; the Denpasar community understands the demands of residential space needs through a spatial transformation based on transformation spatial concepts of Balinese architecture.